Karl Barth"s role in church and politics from 1930 to 1935 - Groenewald, André J. (HTS teologiese studies, 2007)
Karl Barth saw in natural theology a threat to the church of Christ. He was convinced that the so-called “German Christians” under the influence of the National Socialist Party practised natural theology. He advocated the need for the church of Christ to be church according to the Word of God. The church can be true church of Christ when it listens to and obeys the true calling of God. Barth’s critique of an exclusive “Volkskirche” can serve as a corrective for the definition of the Nederduitsch Hervormde Kerk as a “volkskerk”.